(untitled) (Nepalese Medical Journal, 2018)
Clostridium difficile ; a group of spore forming, toxin forming, gram positive anerobel is implicated in hospital associated diarrhea and is the causative agent of infectious diarrhea. It is the most common hospital associated infection in Europe and North America, and is presumed to be as prevalent in the rest of the world. There has been emergence of new virulent strain of C. difficile, identified as BI, NAP1, and toxinotype III and ribotype 027 (subsequently known as BI/NAP1/027) by various typing method in recent years, implicated in dramatic increase in C. difficile infections. Diagnosis is established by presence of C. difficile toxin or C. difficile toxin gene in stool. Lab testing does not distinguish C. difficile infection and asymptomatic carriage. Clinical suspicion and positive stool study confirms a diagnosis. Clostridium Difficile infection, is most common health care associated infection in Europe and North America, and the available studies show it may have similar prevalence in Nepal. Literature review does not reveal any significant study being conducted in Nepal as of now. It warrants further study to exactly determine the incidence/prevalence and its impact in current health care in Nepal. Clinicians need increased awareness and prompt diagnosis to reduce morbidity and further prevention of transmission. Nepalese Medical Journal, vol.1, No. 1, 2018, page: 43-47